Implementation of multicultural values in islamic religious and character education learning to build inter-religious harmony at SMK Negeri 3 Ambon - Ali Litiloly; Hadida Mony (Balai Diklat Keagamaan Ambon, 2025)
This study aims to examine the implementation of multicultural values in the teaching of Islamic Religious Education and Character (PAI-BP) at SMK Negeri 3 Ambon, as well as its contribution to fostering interreligious harmony. The research employs a descriptive qualitative approach, with data collected through observation, interviews, document analysis, and questionnaires. The study subjects include the school principal, Islamic Religious Education teachers, and students of SMK Negeri 3 Ambon. Data analysis was conducted descriptively through the processes of data reduction, presentation, and conclusion. The findings reveal that Islamic Religious Education teachers integrate multicultural values into their teaching by applying inclusive and dialogical approaches, and by connecting learning with local values in students' daily lives both at school and in the community. This approach fosters tolerance, mutual respect, and peaceful coexistence within the multicultural school environment as well as in society. Theoretically, this study strengthens the academic position at the intersection of Islamic education, multicultural studies, and the sociology of education. Practically, the research provides a model for implementing multicultural education based on the Islamic values of Rahmatan lil' Alamin, contextualized and relevant to post-conflict vocational schools. Thus, this study contributes to the development of religious education that is humanistic, democratic, and oriented toward strengthening social cohesion amid national diversity.